Genotype environment interaction and stability analyses of advanced blast resistant rice genotypes derived from crossing MR219 x Pongsu Seribu-2 - Sabri, Raieah Saiyedah; Rafii, Mohd Y.; Chukwu, Samuel C.; Yusuff, Oladosu (Nature Research, 2025)
There is a wide spread of rice blast in Africa, Asia and Latin America, leading to significant yield losses. In addition, the vagaries of climate change makes it necessary to develop a resistant variety capable of adapting to varied environmental conditions. This experiment was conducted to select superior genotypes across environments from the advanced blast resistant rice lines. Eighteen improved blast-resistant rice genotypes that were produced by crossing MR219 (susceptible) and Pongsu Seribu-2 (resistant) were assessed in four distinct environments in Malaysia (UPM Serdang; Tanjung Karang, Selangor; Kota Sarang Semut, Kedah and Tanjung Karang, Selangor). MR219 variety was included as a check variety for yield making a total of 19 genotypes evaluated. Three replications in each environment were used in the randomised complete block design experiment. Data on vegetative, yield, and yield component attributes were recorded. For most of the variables under investigation, analysis of variance showed significant differences between genotypes, environment, and GxE interaction. With the exception of the number of panicles and tillers per hill, low genetic advance was also found for every trait. Positive correlation was found between yield per hectare and other agronomic traits evaluated except days to flowering and maturity, plant height, and number of unfilled grains. Three groups of rice genotypes were identified by stability analyses utilizing both univariate (bi, S2d, σi2, Wi2, YSi) and multivariate stability statistics. The first group comprised genotypes with high mean yield traits and good stability, including G18, MR219, G17, and G11. These genotypes had broad environmental adaptations. The second group’s genotypes, including G1, G6, and G8, were characterised by low stability but high mean yield traits, making them appropriate for cultivation in a specified environment. The third group comprised genotypes such as G7, G9, and G13 that had high stability but a low mean yield characteristic. Environmental discriminate analyses using GGE biplot revealed that Tanjung Karang 1 was the most appropriate environment for most of the genotypes. Blast disease reaction after challenging with inoculum indicates that 11 genotypes proved resistant to the disease while blast disease screening under protected glass house at Mardi and UPM indicated resistance in 13 and 12 genotypes, respectively. Superior genotypes, specifically G18, G17, G11, G14, and G5, were selected from this study because of their stability and high yielding characteristics across mega environments. Breeders could utilize these genotypes for future improvement programmes.